Analytical evaluation of a high-throughput enzyme-linked immunosorbent assay for acrylamide determination in fried foods - Franek, Milan; Rubio, Daniel; Diblikova, Iva; Rubio, Fernando (Talanta, 2014)
The analytical performance and evaluation of a kit-based ELISA for the determination of acrylamide in fried potato and corn chip samples are described. The sample homogenate is subjected to clean-up using SPE, followed by analyte derivatization and ELISA detection. Accuracy, precision and linearity of the ELISA procedure have been validated using spiked samples. Analytical recovery ranged from 91.8% to 96.0% with coefficients of variation below 15%. Good linearity over a wide range of dilution and minimal assay drift was observed within a microtiter plate. IC50 value of the calibration curve was 110 ng/mL, with the limit of detection about 5 ng/mL and dynamic range from 10 to 1000 ng/mL. The high specificity of the ELISA was demonstrated by cross-reactivity study using 11 potential cross-reactants. A good correlation between the results obtained from the ELISA and GC-MS within the concentration range 120-1500 μg/kg was found in the chip samples (r=0.992, n=120). The data demonstrate that the evaluated and validated ELISA has a potential utility in a quick, simple and reliable acrylamide screening analysis for the medium- and large-sized food companies, as well as for residue laboratories and the food industry dealing with improving the chemical safety of foods available to the consumer.
Keywords: Zea mays; Cooking; ELISA kit; vysoká teplota; Hot Temperature; Solanum tuberosum; akrylamid; ELISA; kukuřice setá; Enzyme-Linked Immunosorbent Assay; vaření; reprodukovatelnost výsledků; plynová chromatografie s hmotnostně spektrometrickou detekcí; Acrylamide; Food industry; Reproducibility of Results; Chip samples; kontaminace potravin; Food Contamination; Validation; Food Analysis; Gas Chromatography-Mass Spectrometry; analýza potravin; Screening method